Pengaruh Pelatihan, Kompetensi, Kompensasi, dan Motivasi Kerja terhadap Kinerja Polisi Lalu Lintas Polresta Banjarmasin - Andi Tri Hidayat; Titien Agustina (Jurnal Inovasi Bisnis dan Kewirausahaan, 2020)
Traffic Police Polresta Banjarmasin improves the public services. The public services improvement depend on The Performance. The performance is influenced by traning, competency, compensation, and work motivation. To analyzing and to know the influence of those variables to the performance need the research in police lalu lintas Polresta Banjarmasin. Quantitative method is used in the research. The population is all members of the police. They are 90 persons. Technique of sampling is census. This research sample 63 person. The data collection technique is questioner. Data is analyzed by linier regression analysis. The results of this research shows that traning, competency, compensation, and work motivation have influence significantly to the performance partially. Traning, competency, compensation, and work motivation are need to improve because these variables have influence significantly to the performance improvemet